Effectiveness of Laps-Heuristic Learning With An Open-Ended Approach on Critical Thinking Ability - Baiduri, Baiduri; Putri, Oktavia Kurniawati; Rosyadi, Alfiani Athma Putri (FKIP Universitas Lampung, 2023)
The objective of this study is to assess the efficacy of LAPS-Heuristic learning, coupled with an Open-Ended instructional approach, in enhancing the critical thinking skills of seventh-grade students in a middle school setting. The research employs an experimental methodology with a quantitative framework, specifically utilizing a posttest-only control group design. The study participants consist of seventh-grade students from classes VII A and VII C at SMP MTs Muhammadiyah 1 Malang during the 2022/2023 academic year. Data collection is achieved through a written critical thinking skills assessment. Analysis of the critical thinking ability test results is conducted using the Independent Sample T-test. The findings reveal significant disparities in the critical thinking abilities of seventh-grade students between the experimental group utilizing LAPS-Heuristic learning with an Open-Ended approach and the control group employing conventional teaching methods. Thus, it can be concluded that LAPS-Heuristic learning, when combined with an Open-Ended approach, proves to be an effective strategy for enhancing students' critical thinking skills. Keywords: critical thinking, open-ended, laps-heuristic.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202319